The Effect of Group Guidance Services with Symbolic Modeling Techniques on Improving Prosocial Behavior of SMAN 4 Kota Jambi Students - Khairunisa, Halifah; Rasimin, Rasimin; Yulianti, Yulianti (International Journal of Education, Management, and Technology, 2025)
Prosocial behavior is an important aspect in character development and social interaction at school. If prosocial behavior is not increased, gaps can occur in relationships between students. Therefore, to encourage increased prosocial behavior, counseling services are used, namely group guidance services using symbolic modeling techniques. This research aims to determine the level of prosociality before and after providing services, and the influence of group guidance services. Symbolic modeling techniques on increasing students' prosocial behavior. This research uses quantitative research, experimental methods and variations of pre-experiment, one group Pretest Posttest. The population of this study were students in classes XI.F2, XI.F5 and XI.F6. The sample was selected using a purposive sampling technique based on the criteria recommended by the guidance and counseling teacher, so that 10 students were obtained as a sample. The collection instrument used a questionnaire consisting of 38 items. The analysis techniques used include the KIN (Internal Normative Continuum) approach, normality test, and T-test. The average pretest result of students before being given treatment was 139.7 which was categorized as MEDIUM and after being given treatment the average treatment average was 158.3 which was categorized as HIGH. The T-Test shows that the T-count value is -8.278, which is greater than the T-table, which is 2.228. Sig value. (2-tailed) 0.000, indicating a significant difference between Pretest and Posttest. So it can be concluded that providing group guidance services with symbolic modeling techniques has an effect on increasing students' prosocial behavior.